The effect of foliar application of some micronutrients on the growth and productivity of olive trees “Al Darmlali” variety. - أبو الشملات ربى (Latakia University Journal -Biological Sciences Series, 2022)
This work was carried out during season 2021 on 30 years old trees of olive orchard in Baloran area of Lattakia Governorate on Aldramlali variety, with the aim of studying the effect of foliar spraying for several times with different dates with balanced complex, it contains a number of microelements on yield and oil percentage of olive trees “Al Dramlali variety”. 00The Micronutrients were applied at 3 different times, the first before blooming, the second before blooming and after fruit set, and the third before blooming, after fruit set and in June. The crop was harvested at the end of October. The experiment was designed in a complete randomized design with four replications for each treatment. The statistical analysis of the results, showed the significant increase of the fourth treatement (foliar spraying for three times) of all vegetative indicators compared to the control. Wherease the treatments of foliar spraying (for one, two and three times) showed a significant increase on control which achieved the lowest production and fruit weight (20.72kg/tree,3.96g). The percentage of oil in the fourth treatment (foliar spraying for three times)19.77% and the third treatment (foliar spraying for two times)19.5% reached the highest, while it was only 19.10% in the control